Preface - Biaspamiatnykh, Mikalai; Kačerauskas, Tomas; Małgorzata, Wioletta; Nikiforova, Basia (Creativity Studies, 2008)
“Preface”. LIMES: Cultural Regionalistics, 1(1), p. 3-4.First Published Online: 14 Oct 2010